Activating Transcription Factor 3 and the Nervous System - Anderson, Patrick N. (Frontiers in Molecular Neuroscience, 2012)
It has been recognised for over a century that the ability of axons to regenerate in peripheral nerves is fundamentally greater than that of axons in the brain, spinal cord or optic nerves [early literature was reviewed in (Ramon y Cajal, 1928)]. One factor that contributes to the successful regeneration of the axons in peripheral nerves is the complex cell body response the neurons show to axotomy. That transcription factors must play an important role in enabling neurons to regrow their axons is implicit to the observation that several hundred genes are regulated in neurons during axonal regeneration (Costigan et al., 2002; Boeshore et al., 2004). In addition, similarly large numbers of genes are regulated in the non-neuronal cells present in injured peripheral nerves [especially Schwann cells (Barrette et al., 2010)] and CNS tissue. Of the transcription factors that regulate these changes in gene expression, the function of c-jun is best understood but ATF-3 (also known as LRF-1, LRG-21, CRG-5 and TI-241) is also upregulated in most of the neurons (Fig. 1) and Schwann cells that express c-jun. Indeed, ATF-3 has become a standard marker for neurons axotomised by peripheral nerve injury (Tsuzuki et al., 2001; Yamanaka et al., 2005; Yano et al., 2008; Linda et al., 2011) and its expression by injured neurons is closely correlated with a regenerative response. None the less, surprisingly little is known about the functions of ATF3 in neurons or glia within the injured nervous system, especially when compared with those of its potential binding partner, c-Jun.